(untitled) (Altre Modernità, 2011)
From the early 1970s, the British playwrights of the last thirty years have often turned their attention to existing collections, museums or curatorship. This essay will analyse two plays which are built around a “question of attribution”. Alan Bennett’s A Question of Attribution (1988) puts on stage the art historian Anthony Blunt, director of the Courtauld Institute and personal art advisor to Queen Elizabeth II, who is puzzled by the interpretation and attribution of Titian’s Allegory of Prudence and Triple Portrait. In Bennett’s plot the investigations to ascertain the attribution of the paintings overlap with a Secret Service officer’s enquiries about Blunt, suspected to be a secret spy to the service of Russian KGB. David Edgar’s Pentecost (1994) is an intellectual thriller, where the discovery of a fresco which could be of great relevance for the whole history of Western art is set within the tragedy of Sarajevo. The museological questions of connoisseurship, restoration and conservation are at the core of the play, but besides them the play shows that the museum is deeply compromised with the memory and history of a nation and contributes to define its identity. This essay will investigate the ways through which the two playwrights have adopted a detective story perspective to link the theme of the correct identification of a work of art to questions of identity, memory and national history.